2021
DOI: 10.1021/acsomega.1c04689
|View full text |Cite
|
Sign up to set email alerts
|

Airflow, Fiber Dynamic Whipping, and Final Fiber Diameter in Flush Sharp-Die Melt Blowing with Different Air-Slot Widths

Abstract: Melt streams were attenuated into microfibers by high-speed airflow during melt blowing. The present work explored the effect of air-slot width on the fiber diameter and diameter evenness in flush sharp-die melt blowing. The airflow in different die melt blowing was first numerically simulated by the CFD approach. Then, the fiber dynamic whipping was captured by high-speed photography. Finally, a spinning experiment was implemented and the fiber diameters were measured. The result reveals that the sharp die wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…46,47 Furthermore, Figure 11(a) shows that increasing fiber bending increases fiber attenuation. In line with this observation, other authors reported a close relationship between fiber whipping and diameter; 48 it has been suggested that fiber attenuation is increased by transverse fiber movement to the air field 15 and by the action of an elongational force other than conventional aerodynamic drag. 49,50 Based on the results shown in Figure 13, eq 17 is obtained by considering only the inertial, viscous and aerodynamic forces in eq 14, divided by the reference force and solving this for κ as follows:…”
Section: ■ Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…46,47 Furthermore, Figure 11(a) shows that increasing fiber bending increases fiber attenuation. In line with this observation, other authors reported a close relationship between fiber whipping and diameter; 48 it has been suggested that fiber attenuation is increased by transverse fiber movement to the air field 15 and by the action of an elongational force other than conventional aerodynamic drag. 49,50 Based on the results shown in Figure 13, eq 17 is obtained by considering only the inertial, viscous and aerodynamic forces in eq 14, divided by the reference force and solving this for κ as follows:…”
Section: ■ Resultssupporting
confidence: 67%
“…Furthermore, Figure (a) shows that increasing fiber bending increases fiber attenuation. In line with this observation, other authors reported a close relationship between fiber whipping and diameter; it has been suggested that fiber attenuation is increased by transverse fiber movement to the air field and by the action of an elongational force other than conventional aerodynamic drag. , …”
Section: Discussionsupporting
confidence: 65%
“…Therefore, to increase the spiral motion of the fiber, improvements should be made to the die angle and twisting angle. Jia et al 141 used highspeed photography and SEM to observe the fiber dynamic whipping process, as shown in Figure 13(d), and the fiber diameter, as shown in Figure 14(a) to (c) using sharp-die with different slot widths. The results showed that increasing the slot width led to a decrease in the oscillation frequency of the fiber, a decrease in the envelope angle, an increase in fiber diameter, and an improvement in uniformity.…”
Section: Jet Fieldsmentioning
confidence: 99%